Susceptibility of fluorotic enamel to dental erosion-abrasion - Cristiane Araújo Maia SILVA; Frederico Barbosa de SOUSA; Esperanza Angeles MARTINEZ-MIER; Adam Benjamin KELLY; George J. ECKERT; Anderson Takeo HARA (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract Dental hard tissue conditions can be of pre- or post-eruptive nature, such as enamel fluorosis and erosive tooth wear (ETW), respectively. Dental enamel fluorosis is caused by the chronic and excessive intake of fluoride during enamel development, leading to increased fluoride concentration and increased porosity. ETW has become a common clinical condition and often impairs dental function and aesthetics. This in vitro study tested the hypothesis that fluorotic enamel presents different susceptibility to dental erosion-abrasion. It consisted of a 3×3×2 factorial design, considering a) fluorosis severity: sound (TF0), mild (TF1-2), moderate (TF3-4); b) abrasive challenge: low, medium, and high; and c) erosive challenge: yes or no. A total of 144 human teeth were selected according to the three fluorosis severity levels (n=48), and subdivided into six groups (n = 8) generated by the association of the different erosive and abrasive challenges. Enamel blocks (4×4 mm) were prepared from each tooth and their natural enamel surfaces subjected to an erosion-abrasion cycling model. After cycling, the depth of the lesions in enamel was assessed by profilometry. ANOVA showed that the three-way and two-way interactions among the factors were not significant (p > 0.20). Enamel fluorosis level (p=0.638) and abrasion level (p = 0.390) had no significant effect on lesion depth. Acid exposure caused significantly more enamel surface loss than water (p < 0.001). Considering the limitations of this in vitro study, fluorosis did not affect the susceptibility of enamel to dental erosion-abrasion.